Doxycycline for the treatment of breast cancer-related lymphedema - Brown, Stav; Dayan, Joseph H.; Coriddi, Michelle; McGrath, Leslie; Kataru, Raghu P.; Mehrara, Babak J. (Frontiers in Pharmacology, 2022)
Purpose: Secondary lymphedema is a common complication of cancer treatment for which no effective drug treatments yet exist. Level I clinical data suggests that doxycycline is effective for treating filariasis-induced lymphedema, in which it decreases tissue edema and skin abnormalities; however, this treatment has not been tested for cancer-related lymphedema. Over the past year, we used doxycycline in an off-label manner in patients with cancer-related secondary lymphedema. The purpose of this report was to retrospectively analyze the efficacy of this treatment. Methods: Patients who presented to our lymphedema clinic between January 2021 and January 2022 were evaluated, and barring allergies or contraindications to doxycycline treatment, were counseled on the off-label use of this treatment. Patients who wished to proceed were treated with doxycycline (200 mg given orally once daily) for 6 weeks. After IRB approval of this study, lymphedema outcomes were retrospectively reviewed. Results: Seventeen patients with a mean follow-up of 17.0 ± 13.2 weeks were identified in our retrospective review. Although doxycycline treatment had no significant effect on relative limb volume change or L-Dex scores, we found a significant improvement in patient-reported quality of life. Analysis of patient responses to the Lymphedema Life Impact Scale (LLIS) showed a significant improvement in the total impairment score due to improvements in the physical and psychological well-being subscales (p=0.03, p=0.03, p=0.04, respectively). Conclusions: This small, retrospective study did not show significant improvements in limb volume or L-Dex scores in patients with cancer-related lymphedema treated with doxycycline. However, our patients reported improvements in quality-of-life measures using a validated lymphedema patient-reported outcome instrument. Our results suggest that doxycycline may be of use in patients with cancer-related lymphedema; however, larger and more rigorous studies are needed.